Learning Revolution: The Positive Impact of Computer Simulations on Science Achievement in Madrasah Ibtidaiyah - Habibi, Muhammad Wahab; Jiyane , Lindiwe; Özşen , Zeynep (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aimed to investigate the impact of using computer simulation media on the learning achievement of elementary school students in Natural Sciences, particularly focusing on fourth-grade students at Madrasah Ibtidaiyah Ma'arif Global Blotongan Salatiga. Methodology: The study employed a quasi-experimental design using computer simulation media for experimental group teaching and conventional methods for the control group. The sample was taken using a purposive sampling technique, in which two classes were selected from the class IV population, namely one class as the experimental group and one class as the control group. Each class consists of 30 students. Data collection involved pre-tests, post-tests, and questionnaires to measure student interest and motivation. Analysis was conducted using descriptive and inferential statistical methods. Main Findings: The study found a significant increase in learning achievement among students who used computer simulation media compared to those who did not. Post-test results revealed higher scores for the experimental group. Questionnaire responses indicated increased student interest and motivation in the experimental group. Novelty/Originality of this study: This study contributes to the existing literature by specifically examining the effectiveness of computer simulation media in enhancing learning outcomes in Natural Sciences among elementary school students in a Madrasah setting. It fills a gap in research by providing empirical evidence of the positive impact of such media on student performance and motivation, thus advocating for the integration of technology in primary education.